1998
DOI: 10.1002/(sici)1097-0215(19980812)77:4<511::aid-ijc6>3.3.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

Non‐steroidal anti‐inflammatory drugs and prostate cancer progression

Abstract: Experimental studies have suggested that the biosynthesis of arachidonic acid-derived eicosanoids such as prostaglandin E 2 via the cyclo-oxygenase pathway may play a significant role in supporting cell proliferation in human prostate cancer cell lines. However, the aetiological significance of this for clinical prostate cancer has remained unclear. In particular, the potential for prostate cancer chemoprevention using nonsteroidal anti-inflammatory drugs (cyclo-oxygenase inhibitors; NSAIDs) has received littl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
42
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(47 citation statements)
references
References 4 publications
4
42
1
Order By: Relevance
“…We identified 12 reports (10 manuscripts and two unpublished reports) that met the inclusion criteria (Paganini-Hill et al, 1989;Schreinemachers and Everson, 1994;Neugut et al, 1998;Norrish et al, 1998;Langman et al, 2000;Nelson and Harris, 2000;Habel et al, 2002;Irani et al, 2002;Leitzmann et al, 2002;Menezes et al, 2002;Roberts et al, 2002;Perron et al, 2003). Two other studies were excluded because they evaluated outcomes other than incident prostate cancer: a case -control study that measured the prevalence of prostate cancer in autopsies of analgesics abusers (OR ¼ 0.84; 95% confidence interval (CI): 0.36 -1.98) (Bucher et al, 1999) and a cohort study that measured mortality from male genital cancers (rate ratio ¼ 0.82; 95% CI: 0.56 -1.19) (Thun et al, 1993).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We identified 12 reports (10 manuscripts and two unpublished reports) that met the inclusion criteria (Paganini-Hill et al, 1989;Schreinemachers and Everson, 1994;Neugut et al, 1998;Norrish et al, 1998;Langman et al, 2000;Nelson and Harris, 2000;Habel et al, 2002;Irani et al, 2002;Leitzmann et al, 2002;Menezes et al, 2002;Roberts et al, 2002;Perron et al, 2003). Two other studies were excluded because they evaluated outcomes other than incident prostate cancer: a case -control study that measured the prevalence of prostate cancer in autopsies of analgesics abusers (OR ¼ 0.84; 95% confidence interval (CI): 0.36 -1.98) (Bucher et al, 1999) and a cohort study that measured mortality from male genital cancers (rate ratio ¼ 0.82; 95% CI: 0.56 -1.19) (Thun et al, 1993).…”
Section: Resultsmentioning
confidence: 99%
“…Yet, other studies found no evidence of a dose -effect relationship. (Paganini-Hill et al, 1989;Norrish et al, 1998;Langman et al, 2000). The study that was best equipped to address this issue (Perron et al, 2003), in terms of power and availability of detailed exposure data, reported a stronger inverse association with larger doses of aspirin, but only among participants who used aspirin for X4 years.…”
Section: Resultsmentioning
confidence: 99%
“…S everal epidemiological studies have shown that the use of nonsteroidal antiinflammatory drugs (NSAIDs) is associated with a reduced incidence of clinically detectable prostate cancer (1)(2)(3). The side effects of cyclooxygenase (COX) inhibitors preclude the use of these agents in many elderly men (4).…”
mentioning
confidence: 99%
“…Twenty observational studies with a total of 25 768 participants were included. [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] Characteristics of these studies are presented in Table 1. One study was published in a conference proceeding in 2002, and published again with a smaller sample size in 2005.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…Menezes et al 21 Nelson and Harris 22 Neugut et al 23 Norrish et al 24 Paganini-Hill et al 25 Perron et al 26 Thirteen studies reported the effect of non-ASA NSAIDs with a pooled OR of 0.92 (95% CI 0.85-1.00).…”
Section: Study or Subgroupmentioning
confidence: 99%